Genome-wide association mapping for wood characteristics in Populus identifies an array of candidate single nucleotide polymorphisms - Porth, Ilga; Klapšte, Jaroslav; Skyba, Oleksandr; Hannemann, Jan; McKown, Athena D; Guy, Robert D; DiFazio, Stephen P; Muchero, Wellington; Ranjan, Priya; Tuskan, Gerald A; Friedmann, Michael C; Ehlting, Juergen; et al. (The New phytologist, 2013)
Establishing links between phenotypes and molecular variants is of central importance to accelerate genetic improvement of economically important plant species. Our work represents the first genome-wide association study to the inherently complex and currently poorly understood genetic architecture of industrially relevant wood traits. Here, we employed an Illumina Infinium 34K single nucleotide polymorphism (SNP) genotyping array that generated 29,233 high-quality SNPs in c. 3500 broad-based candidate genes within a population of 334 unrelated Populus trichocarpa individuals to establish genome-wide associations. The analysis revealed 141 significant SNPs (α ≤ 0.05) associated with 16 wood chemistry/ultrastructure traits, individually explaining 3-7% of the phenotypic variance. A large set of associations (41% of all hits) occurred in candidate genes preselected for their suggested a priori involvement with secondary growth. For example, an allelic variant in the FRA8 ortholog explained 21% of the total genetic variance in fiber length, when the trait's heritability estimate was considered. The remaining associations identified SNPs in genes not previously implicated in wood or secondary wall formation. Our findings provide unique insights into wood trait architecture and support efforts for population improvement based on desirable allelic variants.
Keywords: buněčná stěna; wood ultrastructure; alely; jednonukleotidový polymorfismus; fenotyp; genotyp; genetické asociační studie; cellulose; Cell Wall; Genes, Plant; association genetics; Polymorphism, Single Nucleotide; Genotype; Genome, Plant; wood traits; Populus; Wood; lignin; single nucleotide polymorphism (SNP); genom rostlinný; Alleles; dřevo; Genetic Association Studies; rostlinné geny; Phenotype